Air Curtain Design for Landing Gear Noise Reduction - Carroll, Daniel (Trinity College Dublin. School of Engineering. Discipline of Mechanical, Manufacturing and Biomedical Eng, 2023)
This project examined experimentally the use of air curtains as a possible noise reduction technology on aircraft landing gear. Such a concept sought to utilise an upstream planar jet of air to deflect oncoming flow away from the landing gear, hence reducing aerodynamic noise. A thorough design study was first undertaken in the Trinity College fluids lab in which the flow deflection and acoustic performance of various air nozzle concepts and designs were analysed. An open jet wind tunnel was used to generate cross flow, hot wire anemometry was used to characterise flow deflection, and a sound level meter provided acoustic readings. The primary result of this design study was the development of a fundamental nozzle design philosophy, which featured the use of pressurised air to generate choked flow at an outlet consisting of a large number of micro outlet holes. Such a design achieved a uniform planar jet of air with low levels of noise in the audible hearing range, and also achieved high levels of flow deflection compared to alternative designs. Further optimisation of the design through oblique blowing and the use of dual and triple jet configurations improved performance further. This design philosophy was used to develop a series of air curtain nozzles which were tested on a scaled model of the Lagoon nose landing gear in the aeroacoustic wind tunnel at the German Aerospace Centre in Braunschweig, as part of the H2020 collaborative European research project, INVENTOR. Microphone arrays were used to generate frequency spectra and beamforming plots with various orientations relative to the landing gear. While different nozzle configurations showed highly varying degrees of success, noise reductions were observed in the 1-8kHz range, with 10-12dB reductions recorded in some frequency bands. While high frequency noise generated by the nozzles dominated above 10kHz, adding significant noise to the system, the importance of such high frequency noise is unknown as atmospheric attenuation is thought to be substantial for such frequencies, and should therefore be the focus of future work.
Keywords: Air curtains fluid mechanics; noise reduction; aviation